Legal Protection of Beauty Clinic Service Users in Indonesia: Problems and Legal Responsibility - Cahyani Utari; Sunny Ummul Firdaus; Rehnalemkem Ginting (Budapest International Research and Critics University, 2020)
This article aims to examine the form of legal protection and supervision and legal responsibilities related to the implementation of beauty clinic services as well as a description of the existing problems. Research results show that in practice many business actors do not do the things they should do because they are more concerned with material benefits, and less concerned with the dangers of the products they sell. It can be said if every class of consumers who perform treatment at a beauty clinic has the right to get legal protection if there are consequences of the treatment process that is detrimental to him. The rise of malpractice cases, the use of illegal and dangerous drugs, and incompetence of health workers to beauty clinic licenses has become a series of problems that must be addressed by the government through strengthening supervision aspects.